The Feasibility and Safety of Surgery in Patients Receiving Immune Checkpoint Inhibitors: A Retrospective Study - Elias, Alexandra W.; Kasi, Pashtoon M.; Stauffer, John A.; Thiel, David D.; Colibaseanu, Dorin T.; Mody, Kabir; Joseph, Richard W.; Bagaria, Sanjay P. (Frontiers in Oncology, 2017)
Immune checkpoint inhibitors are revolutionizing care for cancer patients. The list of malignancies for which the Food and Drug Administration is granting approval is rapidly increasing. Furthermore, there is a concomitant increase in clinical trials incorporating immune checkpoint inhibitors. However, the safety of immune checkpoint inhibitors in patients undergoing surgery remains unclear. Herein, we assessed the safety of immune checkpoint inhibitors in the perioperative setting at a single center. We conducted a retrospective review of patients who underwent planned surgery while receiving immune checkpoint inhibitors in the perioperative setting from 2012-2016. We collected 30-day post-operative morbidity and mortality utilizing the Clavien-Dindo classification system. We identified 17 patients who received perioperative immune checkpoint inhibitors in 22 operations. Patients were diagnosed with melanoma (n=14), renal cell carcinoma (n=2), and urothelial carcinoma (n=1). Therapies included pembrolizumab (n=10), ipilimumab (n=5), atezolizumab (n=5), and ipilimumab/nivolumab (n=2). Procedures included cutaneous/subcutaneous resection (n=6), lymph node resection (n = 5), small bowel resection (n=5), abdominal wall resection (n = 3), other abdominal surgery (n=3), orthopedic surgery (n=1), hepatic resection (n=1), and neurosurgery (n=2). There were no Grade III-IV Clavien-Dindo complications. There was one death secondary to ventricular fibrillation in the setting of coronary artery disease. Immune checkpoint inhibitors appear safe in the perioperative setting, involving multiple different types of surgery, and likely do not need to be stopped in the perioperative setting. Further studies are warranted to confirm these findings.